PENGARUH LITERASI DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA KEUANGAN DAN KEBERLANJUTAN UMKM DI KABUPATEN WAJO - Nurhasimah, Nurhasimah; Basalamah, Salim; Mahmud, Amir (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development. However, their business sustainability is often hindered by limited financial literacy and poor financial management practices. This study aims to analyze the influence of financial literacy and financial management on the financial performance and sustainability of MSMEs, as well as to examine the mediating role of financial performance in these relationships. A quantitative approach was applied using a survey method involving 354 MSME actors in Wajo Regency, selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS 4.0 software . The results reveal that both financial literacy and financial management have a positive and significant influence on MSMEs’ financial performance. Financial literacy also has a significant direct effect on business sustainability, whereas financial management does not. Furthermore, financial performance significantly mediates the effect of both financial literacy and financial management on MSME sustainability. These findings highlight the importance of enhancing financial capabilities among MSME actors to promote business sustainability, and the need for adaptive policy support aligned with the real conditions faced by small business operators.